2021
DOI: 10.1097/rlu.0000000000003573
|View full text |Cite
|
Sign up to set email alerts
|

Three Different FDG Patterns in Periventricular Nodular Heterotopia Correlated to Video Stereoelectroencephalography

Abstract: A 40-year-old woman with a drug-resistant focal epilepsy underwent cerebral FDG PET in phase 1 presurgical epilepsy study. MRI essentially showed multiple periventricular nodular heterotopias. The stereoelectroencephalography coupled to MRI and FDG PET helped to define the anatomofunctional correlation of the epileptogenic zone network. This procedure brought to light 3 distinct patterns of FDG consumption, corresponding to different anatomoelectroclinical features. This pattern was already found in a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…We found that many patients had hypometabolic GMHs on 18 F‐FDG PET/MRI, heterotopic nodules manifested with a variety of metabolism—ametabolic, hypometabolic, isometabolic, or hypermetabolic in the present work. In line with our results, Popescu et al, Mirandola et al, and Bund et al observed a broad spectrum of FDG uptake patterns in heterotopic nodules in patients with PNH 24,27,32 . Contrarily, many other reports documented that the 18 F‐FDG uptake of GMH is often similar to that of the regular cortex 14,33–37 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that many patients had hypometabolic GMHs on 18 F‐FDG PET/MRI, heterotopic nodules manifested with a variety of metabolism—ametabolic, hypometabolic, isometabolic, or hypermetabolic in the present work. In line with our results, Popescu et al, Mirandola et al, and Bund et al observed a broad spectrum of FDG uptake patterns in heterotopic nodules in patients with PNH 24,27,32 . Contrarily, many other reports documented that the 18 F‐FDG uptake of GMH is often similar to that of the regular cortex 14,33–37 …”
Section: Discussionsupporting
confidence: 92%
“…F-FDG PET/MRI, heterotopic nodules manifested with a variety of metabolism-ametabolic, hypometabolic, isometabolic, or hypermetabolic in the present work. In line with our results, Popescu et al, Mirandola et al, and Bund et al observed a broad spectrum of FDGuptake patterns in heterotopic nodules in patients with PNH 24,27,32. All continuous variables are presented with the mean, standard deviations, and ranges.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…[4][5][6] In a few patients, the PNHs with high FDG uptake on interictal 18 F-FDG PET imaging are the main epileptogenic zones, and removing or destroying the heterotopic nodules alone is sufficient to lead to a seizure-free outcome. [7][8][9][10] Although in other more common situations, several retrospective case series studies 3,11,12 have shown that the aberrant connections formed between the PNH and the adjacent cortical structures appear to be crucial in the epileptogenesis. It is difficult to delineate accurately the epileptogenic zone when the adjacent cortex is negative on MRI.…”
mentioning
confidence: 99%
“…The main associated clinical manifestation of PNH is epileptic seizures, especially resistant focal seizures 4–6 . In a few patients, the PNHs with high FDG uptake on interictal 18 F-FDG PET imaging are the main epileptogenic zones, and removing or destroying the heterotopic nodules alone is sufficient to lead to a seizure-free outcome 7–10 . Although in other more common situations, several retrospective case series studies 3,11,12 have shown that the aberrant connections formed between the PNH and the adjacent cortical structures appear to be crucial in the epileptogenesis.…”
mentioning
confidence: 99%